Inverted mesiodens: case report - MIRANDA,Eneane (2016)
ABSTRACT Mesiodens is the term used for describing the supernumerary tooth that occurs in the maxilla, between the central incisors, in the midline region. These may erupt in the oral cavity or keep themselves impacted. Their presence causes cleaning inadequate, impossibility or difficult of the eruption of the regular teeth and having the aesthetic compromised. This paper aims at showing that early identification of supernumerary teeth, planning and correct approach, allow the preservation of the teeth and adjacent structures. This article presents the clinical case of a seven-year-old child, male, who sought for treatment complaining that teeth 11 didn't appear in the buccal cavity. Clinical and radiographic exams were done and they demonstrated the presence of the supernumerary tooth. The plan of treatment aimed at the correct localization, extraction of this supernumerary tooth and continuous follow up of the case.